Aerial–ground collaborative 3D reconstruction for fast pile volume estimation with unexplored surroundings. (22nd April 2020) - Liu, Sheng; Yu, Jingxiang; Ke, Zhenghao; Dai, Fengji; Chen, Yibin
Fast and accurate pile volume estimation is a very important basic problem in mining, waste sorting, and waste disposing industry. Nevertheless, for rapid changing or badly conditioned piles like stockpiles or landfills, conventional approaches involving massive measurements may not be applicable. To solve these problems, in this work, by utilizing unmanned aerial vehicles and unmanned ground vehicles equipped with a camera, we propose a collaborative framework to estimate volumes of free-formed piles accurately in short time. Compensating aerial- and ground views enable the reconstruction of piles with steep sides that is hard to be observed by single unmanned aerial vehicle. With the help of red-green-blue image sequences captured by unmanned aerial vehicles, we are able to distinguish piles from the ground in reconstructed point clouds and automatically eliminate concave on the ground while estimating pile volume. In the experiments, we compared our method to state-of-the-art dense reconstruction photogrammetry approaches. The results show that our approach for pile volume estimation has proved its feasibility for industrial use and its availability to free-formed piles on a different scale, providing high-accuracy estimation results in short time.